2022
DOI: 10.55131/jphd/2022/200204
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the utilization of health services among patients with hypertension during the Covid-19 pandemic: a cross-sectional study in West Lombok Regency, Indonesia

Abstract: The Covid-19 pandemic has had a wide impact on all areas of life, especially health. One of the serious impacts that need to be addressed is the utilization of health services among people with a history of co-morbidities, the most common of which is hypertension. The purpose of this study was to determine the factors associated with the utilization of health services among patients with hypertension during the Covid-19 pandemic in West Lombok Regency, Indonesia. This study used a cross-sectional study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This outcome is consistent with a similar study conducted in West Lombok Regency, Indonesia, which demonstrated that individuals who received information regarding health services were more likely to utilize them. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome is consistent with a similar study conducted in West Lombok Regency, Indonesia, which demonstrated that individuals who received information regarding health services were more likely to utilize them. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…This outcome is consistent with a similar study conducted in West Lombok Regency, Indonesia, which demonstrated that individuals who received information regarding health services were more likely to utilize them. 30,31 An examination of the consultation process was undertaken by reference to the gatekeeper concept. It focused on the promotion and prevention services that participants could access.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40] The importance of background issues in promoting a positive attitude and healthy practices during the COVID-19 crisis has been described in so many studies across the world. 38,[40][41] The current study included background issues along with individual, family, and social factors predicting preventive behaviors among the rural adults during the pandemic crisis. However, multi-stage sampling from two rural areas might not be sufficient for providing representative samples and avoiding regional variations.…”
Section: Discussionmentioning
confidence: 99%